Recovery of erectile function comparing autologous nerve grafts, unseeded conduits, Schwann-cell-seeded guidance tubes and GDNF-overexpressing Schwann cell grafts - May, Florian; Buchner, Alexander; Matiasek, Kaspar; Schlenker, Boris; Stief, Christian; Weidner, Norbert (Disease models & mechanisms, 2016)
Skip to Next Section - Dissection of the cavernous nerves during radical prostatectomy for prostate cancer eliminates spontaneous erections. Using the rat as an experimental model, we compared the regenerative capacity of autologous nerve grafts and Schwann-cell-seeded nerve guides. After bilateral excision of cavernous nerve segments, cavernous nerves were reconstructed using unseeded silicon tubes, nerve autografts and silicon tubes seeded with either Glial-cell-line-derived (GDNF)-overexpressing or green fluorescent protein (GFP)-expressing Schwann cells (SCs) (16 study nerves per group). Control groups underwent either a sham operation or bilateral excision of cavernous nerve segments without repair. After 12 weeks erectile function was assessed by neurostimulation and intracavernous pressure (ICP) measurement. The reconstructed nerve segments were excised and histologically analyzed. We demonstrated an intact erectile response upon neurostimulation in 25% (4/16) of autologous nerve grafts, in 50% (8/16) of unseeded tubes, in 75% (12/16) of the Schwann-cell-GFP group and in 93.75% (15/16) of the GDNF group. ICP was significantly increased when comparing the Schwann-cell-GFP group with nerve autografts, unseeded conduits and negative controls (P<0.005). In conclusion, Schwann-cell-seeded scaffolds combined with neurotrophic factors are superior to unseeded tubes and autologous nerve grafts. They present a promising therapeutic approach for the repair of erectile nerve gaps.
Gesehen am 13.05.2020